Increasing Digital Competence for Samosir Millennial Generation in The Context of Leading Tourism Promotion - Fatma Lubis; Yovita Sitepu; Hendra Harahap; Raras Sutatminingsih (Talenta Publisher, 2021)
This community service takes the title â€œIncreasing Digital Competence for Samosir Millennial Generation in the Context of Leading Tourism Promotionâ€. The problem that is being solved in this activity is increasing the competence of communication skills in using digital media for tourism promotion purposes. The competencies that you want to develop are the ability to write, photography, videography, and mastery of social media for the promotion of leading tourism in Samosir Regency. Activities carried out in this first year focused on the ability to write features for the Instagram format for SMA Negeri 1 Pangururan students as well as the formation of the Surat Naposo community which will become a pioneer community for tourism promotion among Millennial Samosir. The formation of this community was followed up by the creation of a Surat Naposo Instagram account which will publish writings from community members. The output target to be achieved is the formation of the â€œSurat Naposoâ€ community that has skills in writing, photography, videography, and can manage the web independently. The partner in this activity is the Samosir Regency Tourism Office.